Von Josua bis Jojachin : Untersuchungen zu den deuteronomistischen Geschichtsbüchern des Alten Testaments - Rösel, Hartmut N. (Supplements to Vetus Testamentum,, 1999)
This volume deals with the question of the \'deuteronomistic history\' in the Old Testament and attempts to demonstrate that such a uniform history never existed; the books of Deuteronomy - 2 Kings do not contain such a history. The first part of the book shows that there is no homogenous conceptual framework in the deuteronomistic historical books. For example, different concepts of sin and punishment are found. Even the destruction of Judah and Jerusalem does not represent a \'Leitmotiv\' of divine punishment. The second part of the book deals with problems relating to the various deuteronomistic redactions in the historical books of the Old Testament. In this book the author introduces new perspectives in the discussion of a central problem of Old Testament scholarship.